Etiology of Hospital-Acquired Pneumonia (HAP) and Ventilator-Associated Pneumonia (VAP) in Tertiary-Care Hospitals in Thailand: A Multicenter, Retrospective Cohort Study - Rongrungruang Y; Plongla R; Pleumkanitkul S; Hantrakun V; Khawcharoenporn T (Infection and Drug Resistance)
Yong Rongrungruang,1 Rongpong Plongla,2 Suwapan Pleumkanitkul,3 Viriya Hantrakun,4 Thana Khawcharoenporn5 1Department of Medicine, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand; 2Division of Infectious Diseases, Department of Medicine and Center of Excellence in Antimicrobial Resistance and Stewardship, Chulalongkorn University and King Chulalongkorn Memorial Hospital, Thai Red Cross Society, Bangkok, Thailand; 3Samitivej Hospital Sukhumvit, Samitivej Public Co., Ltd., Bangkok, Thailand; 4Real World Solutions APAC, IQVIA Inc., Bangkok, Thailand; 5Infectious Diseases Unit, Department of Internal Medicine, Faculty of Medicine, Thammasat University, Pathumthani, ThailandCorrespondence: Thana Khawcharoenporn, Infectious Diseases Unit, Department of Internal Medicine, Faculty of Medicine, Thammasat University, Pathumthani, Thailand, 12120, Email kthana@tu.ac.thPurpose: To describe the top three causative organisms of hospital acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) in Thailand.Patients and Methods: This multi-center retrospective cohort study included HAP/VAP patients hospitalized in 2019 in three university-affiliated hospitals and a private hospital in Bangkok, Thailand. Medical records of patients with a documented diagnosis of nosocomial pneumonia (NP) were systematically reviewed to collect data on demographic, clinical, microbiological, and 30-day readmission due to NP.Results: A total of 240 patients were included in the study, comprises patients with VAP (62.9%), HAP (36.7%), and ventilated HAP (vHAP) (0.4%). All of the patients had late-onset NP, occurring after five days of hospitalization with median time to NP of 13 days (interquartile range [IQR] 6– 25 days) from admission. The top three causative pathogens of NP were Acinetobacter baumannii (44.2%), Pseudomonas aeruginosa (34.6%), and Klebsiella pneumoniae (28.3%). A high rate of carbapenem resistance (CR) in A. baumannii (92.5%) was observed. Lower rates of CR were observed in K. pneumoniae (20.6%) and P. aeruginosa isolates (16.9%). Readmission rate due to NP within 30 days after discharge was less than 2% with median time of 4 days (IQR 3– 20 days) after discharge. After diagnosis of NP, 19 patients were transferred to intensive care units with median length of stays of 11 days (IQR 3– 24 days). Fifty-one percent of HAP patients received mechanical ventilation support after the diagnosis of NP with median length of mechanical ventilation use of 12 days (IQR 6– 22 days).Conclusion: A. baumannii, with its significant carbapenem resistance, presents a major HAP/VAP pathogens and imposes a substantial burden on healthcare resources in this study. Implementation of regular surveillance for causative organisms of NP and their susceptibility profiles are critical for the success of HAP/VAP management, and reducing the related burden of healthcare resources.Keywords: nosocomial pneumonia, antimicrobial susceptibility, healthcare-resource burdens, etiologic agents, Thailand